Analysis of COVID-19 Fractional Model Pertaining to the Atangana-Baleanu-Caputo Fractional Derivatives. (10th August 2021) - Ullah, Roman; Waseem, Muhammad; Rosli, Norhayati Binti; Kafle, Jeevan
Abstract : The transmission dynamics of a COVID-19 pandemic model with vertical transmission is extended to nonsingular kernel type of fractional differentiation. To study the model, Atangana-Baleanu fractional operator in Caputo sense with nonsingular and nonlocal kernels is used. By using the Picard-Lindel method, the existence and uniqueness of the solution are investigated. The Hyers-Ulam type stability of the extended model is discussed. Finally, numerical simulations are performed based on real data of COVID-19 in Indonesia to show the plots of the impacts of the fractional order derivative with the expectation that the proposed model approximation will be better than that of the established classical model.